Solubility and availability of micronutrients extracted from silicate agrominerals - Marchi, Giuliano; Guelfi-Silva, Douglas Ramos; Malaquias, Juaci Vitória; Guilherme, Luiz Roberto Guimarães; Spehar, Carlos Roberto; Martins, Eder de Souza (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the solubility of the micronutrients copper, nickel, and zinc, chemically extracted from silicate agrominerals, as alternative sources of potassium for lettuce (Lactuca sativa) and rice (Oryza sativa) cultures, as well as their availability to the plants. The micronutrient contents of five agrominerals (alkaline ultramafic, biotite schist, volcanic breccia, phlogopite schist, and mining by-product from Chapada) were evaluated, after being extracted by the citric acid, hydrochloric acid, diethylenetriaminepentaacetic acid, 3051A, neutral ammonium citrate, and Mehlich-3 methods. The agrominerals, at the doses of 0 (control), 200, 400, and 600 kg ha-1 K, were mixed to soil where lettuce and rice were cultivated. The agrominerals presented a low solubility of Ni, Cu, and Zn, with lower contents in lettuce shoots and rice grains than the corresponding soluble standards in sulfate form. The availability of micronutrients to the plants increased with the use of agrominerals, in comparison with the control. Similarities were observed in micronutrient solubility and availability between the different groups of agrominerals. The solubility and availability of Cu, Ni, and Zn depend on the solubility of the minerals that compose the agrominerals.